Detik.com and Kompas.Com Media Framing Regarding Reporting the Alleged Assault of a Former Indonesian Oriental Circus Performer - Ulfah, Nurul; Rosadi, Ariani; Usman, Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze two mainstream media outlets, detik.com and kompas.com, in framing the alleged exploitation and violence against former Oriental Circus Indonesia (OCI) performers. The analysis was conducted using the Pan and Kosicki framing method, which encompasses four structures: syntactic, rhetorical, thematic, and narrative. Furthermore, the 5W+1H approach was used to explore the basic elements of the reporting. The results show that the two media outlets present very different narrative constructions. Detik.com emphasizes the voices of victims with a human interest approach, framing the issue in the context of conflict between institutions and individuals, and calling for state intervention through human rights institutions. In contrast, kompas.com constructs a narrative of self-defense from the institutional perspective by emphasizing historical legitimacy, visual evidence, and a rhetorical approach focused on clarifying and restoring the reputation of OCI management. These differences in framing demonstrate how the media not only convey facts but also pay attention to public perception through the choice of language structure, narrative perspective, and specific communicative objectives. This research underscores the importance of critical awareness of media framing in issues involving moral conflicts, human rights and institutional interests.